Potensi Industri Mebel Berbasis Pemberdayaan Tenaga Kerja Lokal di Kelurahan Bukir, Kota Pasuruan: Analisis Kontribusi Ekonomi dan Penyerapan Tenaga Kerja - Izzatul Mula; Auliya Ristiani; Diana Novitasari; Rifa Felina; Ningrum Puji Lestari (STIKes Ibnu Sina Ajibarang, 2025)
The furniture industry in Bukir Village, Pasuruan City, is one of the leading small and medium-sized industries (SMIs) that contributes significantly to local economic growth and employment. This study aims to analyze the potential of the furniture industry based on the empowerment of local workers, identify its contribution to the regional economy, and evaluate the level of employment in this sector. The research method employs a qualitative approach with data collection techniques through literature review and structured interviews. The results show that the furniture industry in Bukir Village has grown rapidly since 1980 with the support of the East Java Provincial Technical Implementation Unit (UPT) for Wood. Currently, there are 40 active businesses that can absorb 800-1,200 local workers, equivalent to 85% of the total workforce in the village. This industry uses a made-to-order production system with teak and sonokeling wood as raw materials and has expanded into the export market to Malaysia and other Southeast Asian countries. This study recommends strengthening marketing digitalization, improving human resource skills, and intensifying government support to enhance the competitiveness of the Bukir furniture industry.